Gender dysphoria with homosexuality and comorbid depressive disorder: complexities in concept and management - Bhatia, M. S.; Gautam, Priyanka (International Journal of Research in Medical Sciences, 2017)
Gender identity disorder (GID) and homosexuality are complex entities debated over decades, whether should be categorized as a disorder or not. There are a number of problems specifically related to the criteria of the GID diagnosis like differences in the terms trans-sexualism and GID, failure of the proposed criteria in conceptualizing the whole spectrum of gender variance phenomena, the potential risk of physically invasive examinations to rule out intersex conditions and the application of diagnosis even after hormonal and surgical treatment. We hereby report complexities faced in the case of a male to female transsexual with homosexuality and depressive disorder and its management.